Current position of ALPPS in the surgical landscape of CRLM treatment proposals - Donati, Marcello (Baishideng Publishing Group Co., Limited, 2013)
The Authors summarize problems, criticisms but also advantages and indications regarding the recent surgical proposal of associating liver partition and portal vein ligation (PVL) for staged hepatectomy (ALPPS) for the surgical management of colorectal liver metastases. Looking at published data, the technique, when compared with other traditional and well established methods such as PVL/portal vein embolisation (PVE), seems to give real advantages in terms of volumetric gain of future liver remnant. However, major concerns are raised in the literature and some questions remain unanswered, preliminary experiences seem to be promising. The method has been adopted all over the world over the last 2 years, even if oncological long-term results remain unknown, and benefit for patients is questionable. No prospective studies comparing traditional methods (PVE, PVL or classical 2 staged hepatectomy) with ALPPS are available to date. Technical reinterpretations of the original method were also proposed in order to enhance feasability and increase safety of the technique. More data about morbidity and mortality are also expected. The real role of ALPPS is, to date, still to be established. Large clinical studies, even if, for ethical reasons, in well selected cohorts of patients, are expected to better define the indications for this new surgical strategy.